Local Wisdom Based Body Awareness Education for Early Childhood: A Phenomenological Study of Early Childhood Education Teachers in Jambi City - Indra Bangsawan; Nazurty Nazurty; Fortunasari Fortunasari; Huda Huda; Ridwan Ridwan; Siti Mariah Ulfa (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
This study explores how body awareness education in early childhood is culturally constructed and pedagogically practiced through local wisdom in Jambi City. Body awareness begins with physical recognition and motor coordination, children's understanding of body boundaries, self-protection, dignity, and the social and cultural meaning of the body. Using a phenomenological approach, This study examines the lived experiences of three early childhood teachers at Pembina 1 Kindergarten in Jambi City and three early childhood teachers from RA DWP Raudhatul Athfal in Jambi City. Data were collected through in-depth interviews, lesson observations, and document analysis over a six-month period. The research findings reveal three interrelated themes: teachers' understanding of body awareness as an embodied moral and spiritual education, the integration of Jambi Malay local wisdom and Islamic values ​​into cultural pedagogical practices, and the challenges teachers experience in negotiating cultural taboos, limited learning resources, and curriculum constraints. The results indicate that local wisdom-based learning creates a culturally meaningful space in introducing body safety, self-esteem, and social ethics to children. Theoretically, this research enriches the study of culturally responsive early childhood education by positioning body awareness as a pedagogical and socio-cultural phenomenon shaped by local values, religious narratives, and everyday educational practices.